2019
DOI: 10.14336/ad.2019.0720
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Chronic Temporal Lobe Epilepsy Presenting Constantly Rhythmic and Robust Spontaneous Seizures, Co-morbidities and Hippocampal Neuropathology

Abstract: Many animal prototypes illustrating the various attributes of human temporal lobe epilepsy (TLE) are available. These models have been invaluable for comprehending multiple epileptogenic processes, modifications in electrophysiological properties, neuronal hyperexcitability, neurodegeneration, neural plasticity, and chronic neuroinflammation in TLE. Some models have also uncovered the efficacy of new antiepileptic drugs or biologics for alleviating epileptogenesis, cognitive impairments, or spontaneous recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 117 publications
1
27
0
Order By: Relevance
“…Briefly, the isolation and expansion of human bone marrow-derived MSCs in culture, isolation, and characterization of EVs were done as described in our previous reports [20,24]. Induction of SE in rats was performed using procedures detailed in previous reports [28][29][30]. IN administration of 10 billion EVs was performed 2.5 h after the induction of SE following permeabilization of the nasal mucous membrane with hyaluronidase for 30 min (Figure 1).…”
Section: In-administered Pkh26-labeled Hmsc-evs Pervasively Penetratementioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the isolation and expansion of human bone marrow-derived MSCs in culture, isolation, and characterization of EVs were done as described in our previous reports [20,24]. Induction of SE in rats was performed using procedures detailed in previous reports [28][29][30]. IN administration of 10 billion EVs was performed 2.5 h after the induction of SE following permeabilization of the nasal mucous membrane with hyaluronidase for 30 min (Figure 1).…”
Section: In-administered Pkh26-labeled Hmsc-evs Pervasively Penetratementioning
confidence: 99%
“…After a week of acclimatization in the vivarium, SE was induced in the rats via graded hourly intraperitoneal injections of kainic acid (KA, 5 mg/Kg) for 2-5 h until they displayed either a state of continuous stage 4 seizures characterized by bilateral forelimb clonus with signs of rearing, or a first stage 5 seizure typified by bilateral forelimb clonus with rearing and falling followed by continuous stages 3-5 seizures for over 10 min [28][29][30]42,44]. Rats continuously displayed stages of III-V seizures for two hours after the onset of SE.…”
Section: Induction Of Se In F344 Ratsmentioning
confidence: 99%
“…Status epilepticus (SE) is one of the most severe conditions of epilepsy, which is caused by a hypersynchronous activation of neurons. If SE is untreated, it could result in severe brain damage or death (Hellier and Dudek, 1999;Trinka et al, 2012;Leitinger et al, 2019;Upadhya et al, 2019). In the lithium-pilocarpine model, pilocarpine, which is a directacting cholinergic muscarinic agonist, is administered after pretreatment with lithium to induce continuous seizures; this model is a popular model of acute SE and chronic TLE, which develops within days to weeks after experimental SE (Lévesque et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocyte (dys-) functions have been causally linked to the etiology of TLE (Bedner et al, 2015;Steinhäuser et al, 2016;Deshpande et al, 2020). On a cellular and molecular level, this is paralleled by a selective vulnerability of GABAergic interneurons (Sanon et al, 2005;Upadhya et al, 2019) and reduced glutamate decarboxylase (GAD) as well as glutamine synthetase (GS) activity in astrocytes (Robel and Sontheimer, 2016;Chan et al, 2019), leading to reduced vesicular GABA levels in neurons and subsequently reduced inhibitory input on hippocampal pyramidal neurons (Liang et al, 2006). However, glutamate levels also increase (Luna-Munguia et al, 2011) and a re-emergence of astroglial mGluR5 receptors can be observed (Umpierre et al, 2019).…”
Section: Aberrant Ca 2+ Signaling and Network Excitability Disruptionmentioning
confidence: 99%